Does presence on the UNESCO World Heritage List Support Sustainable Development? A Market-Driven Exploratory Approach - Veghes , Călin (European Journal of Sustainable Development, 2023)
Noting the increasing threats at the address to the cultural and natural heritage and considering their deterioration or disappearing a harmful impoverishment of all the nations, UNESCO adopted fifty years ago, at its 17th General Conference held in Paris, the Convention concerning the protection of the cultural and natural heritage aiming to safeguard it as part of the world's heritage of mankind as a whole. One of its provisions, the inscription on the World Heritage List, has rapidly evolved from recognizing the outstanding universal value to supporting the promotion and capitalization of the heritage sites and their areas by attracting domestic and international visitors interested to discover, explore, enjoy, and engage the cultural heritage, generating the financial resources and creating workplaces to support the social and economic growth. Discussing the impact of presence on the World Heritage List of cultural sites and acknowledging the key role of cultural tourism in the capitalization of cultural heritage, the paper assesses the relationships between the inscription on the List and the sustainable development in terms of the number of incoming tourists, revenues generated from tourism, and the number of the workplaces created in the travel and tourism industry for a group of selected countries. Keywords: Cultural heritage, World heritage list, UNESCO, Cultural marketing, Sustainable development